The reflective educator's guide to mentoring : strengthening practice through knowledge, story, and metaphor - Yendol-Hoppey, Diane; Dana, Nancy Fichtman, 1964- (Corwin Press, a Sage Publications Company, 2007)
Stressing the importance of deep reflection on one's mentoring practice, the authors offer eight models and metaphors that mentors can customize to meet the individual needs of their mentees.